MOLECULAR FINGERPRINTING AND ASSESSMENT OF GENETIC PURITY OF SUNFLOWER (HELIANTHUS ANNUUS L.) HYBRIDS BY USING RAPD AND SSR MARKERS - S. M. BHOSLE; R. L. CHAVHAN; V. R. HINGE; M. K. GHODKE (The Bioscan, 2015)
The investigation pertaining to the hybrid identification in sunflower (Helianthus annuus L.) through RAPD and SSR analysis was conducted on six genotypes and their hybrids. Among fifty three primers comprising 25 RAPD and 18 SSR primers, 2 primers for LSFH-10128 (ORS5 and OPA11), 3 for LSFH-1706 (ORS662, OPC16, OPE16) and 2 for LSFH-7345 (ORS5 and OPA03) were showing both female and male parent specific markers and identified as co-dominant marker for hybrid identification. The genetic relationship study among hybrid and their parental lines revealed their close relationship with 92.0 % to 78.7 % similarity. The parental line CMS-17A was found out grouped at 42 % dissimilarity from members of other clusters in RAPD data. And male parent J/6 was found genetically more divergent and showed 21 % dissimilarity with cluster I and II in SSR data. Thus data analysis could indicate the close similarity of hybrid individual/offspring with their respective parent is the indicative of confirmation of hybrids. This study suggested that molecular marker analysis can be utilized for both reliable and less time consuming identification of hybrids.